Operating System Selection For Information System Practicums: A Comparative Study Of Rocky Linux, Centos Stream, And Ubuntu Using The Analytical Hierarchy Process (eProceedings of Engineering, 2026)
Technology skills development is provided through practicum in the Information Systems Department. But, the fact that various laboratories need varying tools and configurations in their systems makes it highly inconsistent and can affect the experience of practicum for students. Plus, one of the other purposes of this research is to expose students to different operating systems, particularly by exposing them to Linux based systems as part of an approach to expand the students’ technical skills beyond what is most commonly used such as Windows. Thus, this study aims to identify which is the most appropriate OS to be used in supporting laboratory practicum activities in the Department of Information Systems. The research adopted the Analytical Hierarchy Process (AHP) method as its experimental methodology. Of these four criteria, the researcher identified four main categories: compatibility of tools, default system configuration, user experience and performance. The assessment consisted of running each of the practicum modules on three operating systems (Ubuntu, Rocky Linux, and CentOS Stream), noting any issues encountered, as well as a penalty for incomplete modules. The results show Rocky Linux at 58.2%, CentOS Stream at 26.1% and Ubuntu at 15.8%. It was determined that Rocky Linux was the best-suited operating system for use during the practicum, because of its compatibility and performance. Keywords—Operating System, Practicum, AHP, Compatibility, Linux, Laboratory Evaluation